Domain perturbation method and local minimizers to Ginzburg-Landau functional with magnetic effect. (2000) - Jimbo, Shuichi; Zhai, Jian
Abstract : We prove the existence of vortex local minimizers to Ginzburg-Landau functional with a global magnetic effect. A domain perturbating method is developed, which allows us to extend a local minimizer on a nonsimply connected superconducting material to the local minimizer with vortex on a simply connected material.